Ageing in the LHCb outer tracker: phenomenon, culprit and effect of oxygen - Bachmann, Sebastian; Bagaturia, Y.; Blom, M.; Ceelie, L.; van Eijk, D.; Färber, Christian; Haas, Tobias; Mous, I.; Nawrot, A.; Pellegrino, A.; van Petten, O.; Simioni, E.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2010)
The LHCb Outer Tracker (OT) detector has shown to suffer from gain loss after irradiation in the laboratory at moderate intensities. Under irradiation an insulating layer is formed on the anode wire. The ageing is caused by contamination of the counting gas due to outgassing of the glue used in construction namely araldite AY103-1. The gain loss is concentrated upstream the gas flow, and at moderate irradiation intensity only. The ageing rate is reduced by longterm flushing and by the addition of a few percent of O2 to the gas mixture. Furthermore, applying a large positive high voltage (beyond the amplification regime) removes the insulating deposits without damaging the wire surface. This paper presents both the characteristics of the ageing phenomenon and the beneficial treatments.
Online verfügbar 10 November 2009
Gesehen am 28.11.2022